1980
DOI: 10.2337/diacare.3.3.489
|View full text |Cite
|
Sign up to set email alerts
|

Maximal Tolerated Insulin Therapy in Gestational Diabetes

Abstract: Beginning in 1963 we have administered fast-acting insulin in three daily injections up to the maximal tolerated dose (M.T.D.), which can be defined as the highest quantity that can be given without bringing about hypoglycemic disturbances. This therapeutic criteria was applied both to gestational (280 pregnant women) and clinical (199 pregnant women) diabetes. M.T.D. was established on first admission to hospital and afterward controlled weekly in the outpatient clinic and during short periods of hospitalizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
3

Year Published

1980
1980
2000
2000

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(25 citation statements)
references
References 6 publications
1
21
0
3
Order By: Relevance
“…The concept of 'maximal tolerated insulin dose' which was introduced by Roversi [25] over 20 years ago did much to encourage the more enthusiastic use of insulin, and in particular demonstrated the often very considerable increase in insulin dose needed in the pregnant diabetic mother to achieve normoglycaemia. The ability to self-monitor blood glucose has simply improved the ability to demonstrate normal glucose values.…”
Section: Internal Medical Aspectsmentioning
confidence: 99%
“…The concept of 'maximal tolerated insulin dose' which was introduced by Roversi [25] over 20 years ago did much to encourage the more enthusiastic use of insulin, and in particular demonstrated the often very considerable increase in insulin dose needed in the pregnant diabetic mother to achieve normoglycaemia. The ability to self-monitor blood glucose has simply improved the ability to demonstrate normal glucose values.…”
Section: Internal Medical Aspectsmentioning
confidence: 99%
“…This has resulted in much confusion and a lack of comparability between studies [53][54][55][56][57][58][59][60][61][62][63] [66,67]. Data obtained using each of these methods has been associated with maternal-fetal outcome [64,[68][69][70][71], and in some cases, to long-term outcome in the child [72][73][74][75]. The differences between cut off points used in different schemes (e. g. WHO and DPSG-EASD) reflect the inherent arbitrariness of cut off points for classifications based on continuously distributed data in the absence of evidence for a threshold predicting adverse outcomes in the mother or child.…”
Section: Diagnosis Of Diabetes In Pregnancymentioning
confidence: 99%
“…Calory intake differed from patient to patient. According to our criteria [5,6,7,8,9, 10] each < patient had been invited to choose her first menu without any restriction ön quality or quantity. Retrospective analysis showed that the calory content averaged 1900 cal/24 hours and composition, protein glucose and lipids, were respectively 15.5%, 53.2%, 31.3%, with fluctuatiqns of ± 10% in most cases [8].…”
Section: Methodsmentioning
confidence: 99%
“…They have already been reported [l, 5,6,7,8,10] and consist of: 1) a reduction in perinatal mortality (P.M.) to values (total P M. 2.9%, corrected P M. 1.9%) of the general P.M. (in 1975 total PM. of the general population in the Clinic 2.5%); 2) near disappearance of foetal macrosomia (3.3% above 4000 g) and normalization of birth weight(newbornweight does not differ from normal newbom weight) [9]; 3) a normal incidence of pathological Symptoms in newborn infants which were not however severe (respiratoiy distress syndrome 0.6%, hypoglycemia 13.4%); 4) reduction of caesarian sections to 24.6%; 5) delivery time did not have to be systematically brought forward, but only in cases where poor conditions of the foetus were apparent (labour induced in 9.6% of cases): 74.7% of the cases gave birth after the 38th week of gestation. The M.T.D.…”
Section: Introductionmentioning
confidence: 96%